The mediated world : a new approach to mass communication and culture - Mindich, David T. Z., 1963- (Lanham Rowman & Littlefield, 2020)
"Written for students to engage in how we communicate with one another, how we understand our world, and how media shapes us. Using stories of our media and culture, this book offers historical context, integrates new media advances into each chapter, and takes an interdisciplinary approach to the study of communication"--
A new approach to media in your life -- Growing up in a mediated world -- How we acquire language : communication and community -- The brain and the birth of writing -- Printing, the mass public, and the mass private -- Newspapers in a digital media world -- Magazines and the construction of the story -- Going global : the telegraph -- Radio, music, and the soundtrack of our lives -- Writing images and movement: photography -- Movies and the dream factory -- Television : broadcasting and narrowcasting -- Advertising -- Public relations -- Law and ethics, media and journalism -- Media and agenda setting in the political sphere -- The new media explosion -- In the midst of a revolution, imagining the future.
Includes bibliographical references and index.
Keywords: Mass media and culture; Communication and culture; Mass media -- Social aspects; Communication -- Social aspects